Building stakeholder engagement in sustainable solutions – the strategic advisory panel on selenium management - Swanson, S; Abbott, R; Funk, W; Kirk, L; McKenna, G; Ohlendorf, H; Sandy, T (Mine Closure 2011: Sixth International Conference on Mine Closure, 2011)
The Strategic Advisory Panel on Selenium Management is a broadly-based group of experts who have achieved success via independent, transparent stakeholder engagement with full collaboration across diverse disciplines. The panel was formed in January 2010 to assist Teck Coal and its stakeholders in finding a sustainable approach to the management of selenium released from Teck’s metallurgical coal mines in south-eastern BC and north-western Alberta. The panel’s charter stipulated that the panel would operate independently and would release a strategic plan for the management of selenium within six months. While part of the panel’s work was highly technical, an equally important activity was active engagement with stakeholders. Selenium is a controversial topic with significant technical uncertainties, and often with strongly held views by potentially affected people (concerning their health or effects on ecosystem services). Past attempts to deal with these uncertainties had not succeeded in producing an acceptable plan for managing selenium loadings to the watershed, which were steadily increasing. Trust among stakeholders was low. The panel used one-on-one meetings, workshops, site visits, and community meetings to reach out to Teck personnel, regulators, First Nations, NGOs, elected officials, and representatives of key stakeholder groups such as fly fishers. The panel’s engagement activities, combined with the release of the strategic plan report without prior review by stakeholders (including Teck) produced a substantial increase in trust and engagement. The rapid acceptance of the report by the CEO of Teck Coal added to that trust. The involvement of stakeholders has continued into the implementation phase, which includes management of selenium at legacy waste dumps, incorporation of new operating procedures at active mines, inclusion of alternative mine and waste management practices for proposed expansions and new mines, and Teck’s continued engagement with a community-based watershed-health advocacy group. The continued engagement of stakeholders is an integral part of Teck’s commitment to sustainable mining. The panel’s experience shows that independent advisory panels can be an effective catalyst for trust-building, especially if their activities truly are governed by sustainability principles.